Stimulation of naïve B cells with a fusion protein consisting of FlaA and Bet v 1 induces regulatory B cells ex vivo. Issue 3 (20th October 2022) - Goretzki, Alexandra; Lin, Yen‐Ju; Meier, Clara; Dorn, Britta; Wolfheimer, Sonja; Jamin, Annette; Schott, Maike; Wangorsch, Andrea; Vieths, Stefan; Jakob, Thilo; Scheurer, Stephan; Schülke, Stefan
Abstract: Background: The experimental fusion protein rFlaA:Betv1 was shown to efficiently suppress allergen‐specific sensitization in mice. However, the detailed mechanism of rFlaA:Betv1‐mediated immune modulation is not fully understood. In this study, we investigated the effect of rFlaA:Betv1 on naïve murine B cells. Methods: Immune modulating capacity of rFlaA:Betv1 was screened in IL‐10 reporter mice. B cells were isolated from spleens of naïve C57Bl/6, TLR5 −/−, or MyD88 −/− mice, stimulated with rFlaA:Betv1 and controls, and monitored for the expression of the regulatory B cell markers CD1d, CD24, CD38, and surface IgM by flow cytometry. Secreted cytokines, antibodies, and reactivity of the induced antibodies were investigated by ELISA and intracellular flow cytometry. Suppressive capacity of rFlaA:Betv1‐stimulated B cells was tested in mDC:CD4 + T cell:B cell triple cultures. Results: Upon in vivo application of rFlaA:Betv1 into IL‐10‐GFP reporter mice, CD19 + B cells were shown to produce anti‐inflammatory IL‐10, suggesting B cells to contribute to the immune‐modulatory properties of rFlaA:Betv1. rFlaA:Betv1‐induced IL‐10 secretion was confirmed in human B cells isolated from buffy coats. In vitro stimulation of naïve murine B cells with rFlaA:Betv1 resulted in an mTOR‐ and MyD88‐dependent production of IL‐10 and rFlaA:Betv1 induced Bet v 1‐reactive IgG production, which was not observed for IgA. rFlaA:Betv1‐stimulated B cells formed a CD19 + CD24 + CD1d + IgM + CD38 + Breg subpopulation capable of suppressing Bet v 1‐induced TH2 cytokine secretion in vitro. Conclusion: rFlaA:Betv1 can act as a thymus‐independent B cell antigen, stimulating the mTOR‐ and MyD88‐dependent differentiation of B cells displaying a regulatory phenotype, IL‐10 secretion, antigen‐binding antibody production, and a suppressive capacity in vitro. Abstract : Stimulation of naive ex vivo‐isolated B cells with rFlaA:Betv1 results in a MyD88‐ and mTOR‐dependent, but TLR5‐independent differentiation of regulatory B cells. Regulatory B cells were shown to be CD19 + CD24 + CD1d + IgM + CD38 + and secreted both anti‐inflammatory cytokine IL‐10 and allergen‐specific IgG antibodies. In co‐cultures with TH2‐biased Bet v 1‐specific CD4 + T cells, rFlaA:Betv1‐stimulated B cells suppressed Th2 responses.Abbreviations: BCR, B cell receptor; mDC, myeloid dendritic cell; MyD88, myeloid differentiation primary response 88; mTOR, mammalian target of rapamycin; rFlaA:Betv1, fusion protein of the TLR5‐ligand flagellin A and the major birch pollen allergen Bet v 1; TLR5, Toll‐like receptor 5.